Conservatism and international IPO underpricing - Boulton, Thomas J; Smart, Scott B; Zutter, Chad J (Journal of International Business Studies, 2017)
We study the impact of country-level accounting conservatism on international IPO underpricing. Examining 13,285 IPOs from 36 countries, we find that IPOs are underpriced less in countries in which existing public firms practice more accounting conservatism. The link between conservatism and underpricing is robust to alternative measures of conservatism, country mean regressions, sample country exclusions, and endogenous treatment models. Consistent with the hypothesis that conservatism reduces underpricing by mitigating the impact of information asymmetries, we find that higher country-level conservatism is associated with lower country-level PIN values and that the negative relation between conservatism and underpricing is strongest for IPOs involving small firms in which information asymmetries are likely to be high. Lastly, we find evidence that legal origin, a factor linked to the practice of conservatism, influences the relations between underpricing and conservatism.